MEDIA LITERACY AND THE EVOLUTION OF INFORMATION CULTURE AND ITS IMPORTANCE IN SOCIETY. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Forming the culture of using the media space, the Internet and social networks among young people is the foundation of today's modern information space and is an integral part of human social and cultural life. Because the concept of information is specific to space and time, it appears in various forms as a periodic phenomenon. Nowadays, due to the increased flow of information in society, the process of "getting tired of" information, consuming it without analyzing it, has arisen. The urgency of understanding, evaluating and forming critical thinking of information received in the global information space is explained.